Optimizing the Role of Stakeholders: Development of Coffee Gastronomic Tourism in Malang - Hamdan Yuwafi; Luchman Hakim; Aminudin Afandhi (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
The development of a tourism site necessitates the participation of various actors. This study's goal is to analyse stakeholders by identifying, categorizing, and describing their interrelationships, as well as the difficulties they encounter, and then optimizing them to develop coffee gastronomy tourism in Malang. The research was conducted in Harjokuncaran Village-Sumbermanjing Wetan (AMSTIRDAM region) by using observation of events and interviews with stakeholders (as primary data sources), and a literature review and documentation (as secondary data sources). The acquired data were then evaluated using qualitative descriptive and pentahelix modeling methods. We identified the engaged stakeholders as primary stakeholders, secondary stakeholders, and key stakeholders. Each stakeholder serves as a coordinator, implementer, facilitator, policymaker, and accelerator. The involved parties can be classified into five categories: the community, the government, the private sector, academics, and media activists. According to the results of the pentahelix modeling, the media and academics, as well as the private sector and academia, do not have a direct relationship, whereas other stakeholders have direct relationships based on mutual trust and respect. The efforts should be optimized by the involvement and participation of stakeholders, enhancing coordination and collaboration among stakeholders, and conducting tourism management.